Spell bound - Armstrong, Kelley (Plume, 2012)
Someone has cut off the powers of headstrong young witch Savannah Levine and there's a witch-hunter out to kill her. Savannah, who just tackled her first murder case as a private investigator, now has to rely on mundane skills and her half-demon best friend, Adam, to turn the tables on her would-be killer and recover her magic.
Keywords: Paranormal fiction; Canadian; Fantasy fiction; Canadian; Occult fiction; Fantasy fiction; Witches